The Effect of Psychological Intervention on Nutrient Status of Perioperative Patients with Lung cancer - Fen XUE; Fang HUANG (Tehran University of Medical Sciences, 2018)
Background: To investigate the effect of psychological intervention on nutrient status of perioperative patients with lung cancer. Methods: Overall, 176 lung cancer patients admitted to Shanghai Pulmonary Hospital, Shanghai China from 2015 to 2016 were divided into control group (n=88) and study group (n=88). Conventional nursing strategy was adopted for patients in control group, while psychological nursing strategy was implemented for those in the study group, and the specific nursing efficiency was compared between the two groups. In addition to the assessment with Symptom Checklist 90 (SCL-90) and Quality of Life Questionnaire-Core 36 (QLQ-C30), patients were required to fulfill the evaluations with nutrition risk screening 2002 (NRS2002) and Patient-Generated Subjective Global Assessment (PG-SGA). Results: After nursing care, significant amelioration in scores of SCL-90 and QLQ-C30 of patients were seen in the study group (P<0.05). In the study group, the scores of NRS2002 and PG-SGA were all lower than those in the control group (P<0.001). Besides, PG-SGA score was also significantly correlated with the levels of serum total proteins, serum albumin, hemoglobin, reduction in diet and weight (P<0.01), while only reduction in diet and weight was obviously correlated with the score of NRS2002 (P<0.01). Moreover, a significant correlation was identified between the scores of PG-SGA and NRS2002 (P<0.01). Conclusion: Psychological intervention could effectively alleviate the psychological stress response and ameliorate the nutrient status of lung cancer patients in perioperative period, thereby reducing the negative feelings and increasing the life quality of patients.